STRATEGI KOMUNIKASI DALAM PROMOSI (Studi Kasus Promosi Prodi KPI STAIN Mandailing Natal): Studi Kasus Prodi KPI STAIN Mandailing Natal - zubaidah; Marlina; Desiana (LP3M IAI Al-Qolam, 2024)
This research aims to explore and analyze the promotional strategies implemented by the Islamic Communication and Broadcasting Study Program at STAIN Madina in increasing new students. Competition is increasingly fierce in the world of higher education, so it is important for academic institutions to implement effective promotional strategies to attract the attention of prospective students. The research method used is descriptive qualitative by looking at and understanding the subject and object of research which includes interviews with sources, and observing the Study Program based on facts that appear as they are. The research results show that STAIN Madina implements various promotional strategies which include the use of social media, MoU and MUA cooperation for the Islamic Communication and Broadcasting Study Program, improving website quality and program activities for the Islamic Communication and Broadcasting Study Program. However, behind all this, there are obstacles in developing the promotional strategy, namely budget limitations, competition with other universities, public perception, limited human resources, technological infrastructure and the quality of study programs. The conclusion of this research is that a combination of integrated and adaptive promotional strategies can significantly increase new students, noting the importance of regular evaluation and adjustment of strategies. These findings are expected to provide valuable insights for other higher education institutions in formulating effective promotional strategies.